Development of a new ictal EEG source imaging technique using recursive approach for presurgical evaluation of focal epilepsy / Abu Hasnat Mohammad Ashfak Habib - Abu Hasnat Mohammad , Ashfak Habib (2018)
Electroencephalography source imaging (ESI) is a promising tool for localizing the cortical sources of both ictal and interictal epileptic activities. Although ictal EEG is difficult to analyze, it is believed to be more reliable than interictal ESI. Ictal ESI techniques can be categorized as Independent Component Analysis (ICA) based techniques and less stable non-ICA based classical techniques. Existing ICA-based techniques are highly dependent on visual inspection and user’s feedback. This thesis presents the development of a new enhanced automatic ICA-based ictal ESI technique for epileptic focus localization in patients with refractory focal epilepsy. The proposed technique decomposes ictal EEG recursively, eliminates unwanted portion in every recursion cycle, and selects a significant ictal Independent Component (IC) at the final recursion cycle with the help of a unique quantitative feature of decomposed EEG. Back projected EEG is regenerated from that selected IC and epileptogenic focus is estimated from that regenerated EEG. Fifty sets of simulated ictal EEG and 8 patients’ real ictal EEG were used for validation. Epileptogenic foci were estimated form those datasets by using the proposed technique and other two ICA-based techniques. Simulated-EEG-sources were compared with a known dipole location and real-EEG-sources were compared with the sites of successful surgery for the performance evaluation of the three techniques. Average distance of the estimated dipole from the original dipole for the proposed technique was 12.86 mm which was shorter than the half of the average distances for other two techniques. The real-EEG-sources estimated by the proposed technique were fully lateralized with the corresponding sites of surgery and the concordance rate (87.50%) was also higher than that of other two techniques (37.5% and 12.55%). These findings show that the proposed ictal ESI technique may provide a cost-effective substitute for other costly diagnostic modalities.